Health Risk Assessment of PM2.5-bound Components in Beijing, China during 2013–2015 - Tianchu Zhang; Yangfan Chen; Xiaohong Xu (Aerosol and Air Quality Research)
Abstract Risk assessment methods of the US Environment Protection Agency (U.S. EPA) were employed to estimate lifetime cancer risk in Beijing using the following fine particulate matter (PM2.5) components: six elements and 16 U.S. EPA priority polycyclic aromatic hydrocarbons (PAHs), and lifetime non-cancer hazard quotients (HQ) using 11 elements, based on data collected in Beijing during 2013–2015. The three-year average PM2.5 mass concentration was 82 µg m–3. Both lifetime cancer risk (1.9E-4) from exposure to ambient PM2.5-bound elements and PAHs and non-cancer HQ (18) from exposure to ambient PM2.5-bound elements in Beijing were much higher than the corresponding U.S. EPA acceptable levels. Cancer risks by source were, in descending order, road dust (7.3E-5), fossil fuel combustion (4.4E-5), vehicle exhaust (3.8E-5), soil dust (8.4E-6), metal processing (8.2E-6), secondary sulphur (8.0E-6), and biomass burning (6.4E-6). Cancer risks by PM2.5 component were, in descending order, As (1.1E-4), Cr(VI) (3.4E-5), total PAHs (1.5E-5), Pb (1.1E-5), Co (8.4E-6), Ni (3.9E-6), and Cd (3.9E-6). HQ by PM2.5-bound elements were, in descending order, Cl (14), As (1.8), Pb (0.94), P (0.81), Cd (0.22), Mn (0.22), Ni (0.18), Ba (0.1), Cr(VI) (0.03), Co (0.01), and Se (0.002). Fossil fuel combustion and vehicle exhaust were the top two sources, accounting for 77% of total HQ. HQ by target organ were, in descending order, respiratory (15), reproductive (1.8), nervous (1.2), renal (0.22), fetus (0.1), and alimentary system (0.002). The seasonal variations in PM2.5 mass concentrations, risks, as well as source and element contributions were largely due to increased coal combustion in winter.